Harmonisation of labour laws: an arduous journey for ASEAN. (2nd January 2020) - Sale, Jonathan
ABSTRACT: Of late, there have been efforts towards regional harmonisation of industrial relations (IR) systems in the Association of Southeast Asian Nations (ASEAN). IR systems are closely linked to labour law systems. This research looks into ASEAN labour law systems as plausibly occupying loci or points along a continuum. At one end might be systems influenced by the legal family of civil law; at the other could be those swayed by the legal family of common law. In between, there is likely a gamut of systems having endogenous origins, hybrids of civil Law and common law, trichotomies that include customary or indigenous law, among others. Is it possible to harmonise or transfer labour laws across ASEAN? What have been the approaches to labour market regulation? Using a comparative case study method, this paper attempts to answer these questions and delves into examples from the Philippines and Malaysia to show that the path to harmonising or transferring labour laws within ASEAN is long and difficult in light of critical stumbling blocks, such as methodological nationalism, legal endemism, diverging epistemological assumptions, and modes of legal reasoning of labour laws.